Proceedings of the 7th ACM International Conference on Bioinformatics, Computational Biology, and Health Informatics 2016
DOI: 10.1145/2975167.2985688
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Spatio-temporal Visual Analysis of Cluster Evolution in Electrocorticography Data

Abstract: We present ECoG ClusterFlow, a novel interactive visual analysis tool for the exploration of high-resolution Electrocorticography (ECoG) data. Our system detects and visualizes dynamic high-level structures, such as communities, using the time-varying spatial connectivity network derived from the high-resolution ECoG data. ECoG ClusterFlow provides a multi-scale visualization of the spatio-temporal patterns underlying the time-varying communities using two views: 1) an overview summarizing the evolution of clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Other techniques like seeNet [27] use abstraction techniques to identify and characterize major events in the network flow data and the tool by Teoh et al [28] focuses on merging and utilizing multiple visualization views to explore complementary aspects of the data. Visual methods in other domains such as brain networks employ linked visualization views [29,30] and flow-based techniques [31,32] to better understand brain activity.…”
Section: Network Analysis and Visualizationsmentioning
confidence: 99%
“…Other techniques like seeNet [27] use abstraction techniques to identify and characterize major events in the network flow data and the tool by Teoh et al [28] focuses on merging and utilizing multiple visualization views to explore complementary aspects of the data. Visual methods in other domains such as brain networks employ linked visualization views [29,30] and flow-based techniques [31,32] to better understand brain activity.…”
Section: Network Analysis and Visualizationsmentioning
confidence: 99%
“…With the development of technology, neurophysiological activities from brain, heart, and eye movement can be recorded and analyzed to reflect the mental state objectively in a noninvasive way [13]. Previous studies have confirmed that signals such as near-infrared spectroscopy (NIRS), functional magnetic 2 of 15 resonance imaging (fMRI), electrocorticography (ECoG), or electroencephalography (EEG) are closely correlated with brain status and can provide a useful way to assess cognitive load [14][15][16][17][18]. Among these physiological signals, EEG has been widely concerned by researchers because of its high time resolution, noninvasiveness, convenience, security, cheapness, and portability [19,20].…”
Section: Introductionmentioning
confidence: 99%